Electrolytic manganese residue-fly ash-based building thermal insulation material and preparation method thereof
By combining electrolytic manganese slag with fly ash, and using alkali excitation reaction and foaming treatment technology, building insulation materials with excellent insulation properties are prepared, which solves the problems of resource utilization and harmless treatment of electrolytic manganese slag, and reduces building energy demand and material preparation costs.
Patent Information
- Application Number
- CN202411798758.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-15
AI Technical Summary
When using electrolytic manganese slag for building materials, the prior art mainly focuses on mechanical strength, and high process technical requirements, low economic added value of the product, making it difficult to effectively solve the problems of resource utilization and harmless treatment of electrolytic manganese slag.
By combining electrolytic manganese slag with fly ash, using alkali excitation reaction to prepare geological polymers, foaming, and molding through medium and low temperatures, building insulation materials with excellent insulation properties were prepared.
It effectively improves the insulation and insulation performance of building enclosure structures, reduces building energy demand, solves the problems of electrolytic manganese slag resource utilization and harmless treatment to a greater extent, and reduces the cost of material preparation, and has significant environmental protection advantages.
Smart Images

Figure BDA0005177481540000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparing building thermal insulation materials from electrolytic manganese slag solid waste, and in particular to an electrolytic manganese slag-fly ash-based building thermal insulation material and a preparation method thereof. Background Art
[0002] Electrolytic manganese slag is a byproduct produced in the process of electrolytic manganese production, mainly derived from a series of treatment processes after the reaction of manganese carbonate ore powder with sulfuric acid. As the main waste generated in the process of metallic manganese production, the amount of electrolytic manganese slag piled up in the open air has reached millions of tons, posing a great potential danger to the environment and ecosystem. Since electrolytic manganese slag contains a variety of heavy metals that are harmful to the human body, such as cadmium, lead, zinc, nickel, etc., how to harmlessly treat it and recycle it has become a major problem that needs to be solved urgently.
[0003] Existing studies have shown that the use of electrolytic manganese slag in building material production, road base materials and environmental landfill has certain effects. As a raw material for building materials, manganese slag can be consumed in large quantities, turning it into treasure. In the prior art, the patent application with publication number CN118388154A proposes a method for utilizing electrolytic manganese slag-chromium slag synergistic resources and a prepared gelling material, which includes: S1. Mixing a portion of carbide slag (the main component is calcium hydroxide) with electrolytic manganese slag slurry, deammoniating, obtaining deammoniated manganese slag and ammonia, and recovering ammonia; S2. Mixing the deammoniated manganese slag with chromium slag and another portion of carbide slag and ball milling to obtain a mechanically modified mixed raw material; S3. Mixing the mechanically modified mixed raw material with water to obtain a medium-calcium system gelling material; The medium-calcium system gelling material is prepared by the synergistic solidification of electrolytic manganese slag-chromium slag, realizing the harmless treatment and building material utilization of electrolytic manganese slag and chromium slag, and reducing the pollution of the surrounding environment and the occupation of land resources caused by the accumulation of electrolytic manganese slag. For example, the patent application with publication number CN117865625A proposes an electrolytic manganese slag-red mud concrete material, whose components include electrolytic manganese slag-red mud modified micropowder, adjusting agent, fine aggregate and coarse aggregate, etc.; the raw material components of electrolytic manganese slag-red mud modified micropowder include electrolytic manganese slag, red mud (iron oxide, silicate, calcium hydroxide, etc.), quicklime, ammonia nitrogen curing agent, and heavy metal ion stabilizer. This scheme mainly utilizes the sulfate in the electrolytic manganese slag and the alkali in the red mud, which can react with the adjusting agent to undergo alkali-complex salt excitation, accelerate the hydration rate and reaction degree of the material, and improve the strength of the cementitious material. The generated calcium sulfonate and zeolite hydration products are used to block the pores of the concrete and improve the density; and combined with fine aggregate and coarse aggregate, the flexural tensile strength and wear resistance of the concrete are improved. In addition, by modifying the electrolytic manganese slag and red mud, the harmless treatment of the electrolytic manganese slag and red mud is achieved, and the pollution of the concrete material to the environment is reduced.
[0004] However, when the electrolytic manganese slag is used for building materials, the above schemes are mostly used to prepare structural building materials, that is, only mechanical strength is considered. If these schemes are to be put into practical use, they have high requirements for process technology and low economic added value of products. Therefore, it is necessary to optimize and adjust the use direction of electrolytic manganese slag in building materials. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides an electrolytic manganese slag-fly ash-based building thermal insulation material and a preparation method thereof, which utilizes an alkali-excited reaction to prepare a geopolymer, which is then foamed and formed by medium and low temperature curing; the present invention uses electrolytic manganese slag as a building thermal insulation material, while absorbing a large amount of manganese slag, effectively improves the thermal insulation performance of the building envelope structure and thereby reduces the energy demand of the building, and largely solves the problem of resource utilization and harmless treatment of electrolytic manganese slag.
[0007] (II) Technical solution
[0008] In a first aspect, the present invention provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: a basic raw material, an alkali activator, a foam stabilizer and a foaming agent;
[0009] The basic raw material is a mixture of electrolytic manganese slag and fly ash, wherein the electrolytic manganese slag accounts for 50%-100% by weight; the electrolytic manganese slag is only pre-treated by drying, grinding and sieving, and the powder particle size is 60-120 meshes; the powder particle size of the fly ash is 200 meshes;
[0010] The alkaline activator is prepared by mixing sodium hydroxide, water glass and water;
[0011] The foam stabilizer is soap powder or sodium stearate, with a particle size of 60-120 mesh;
[0012] The foaming agent is at least one of hydrogen peroxide, aluminum powder and sodium percarbonate.
[0013] Among them, the powder particle size of 60-120 mesh means that the powder particles are small enough to pass through a 60-mesh sieve, but cannot pass through a 120-mesh sieve. The powder particle size of 200 mesh means that the particle size of the powder is small enough to pass through a 200-mesh sieve, and the particle size is ≤74μm.
[0014] According to a preferred embodiment of the present invention, the amount of the foaming agent is directly related to the type of the foaming agent; specifically, when the foaming agent is hydrogen peroxide, the amount thereof is 2-3% of the mass of the basic raw material; when the foaming agent is aluminum powder, the amount thereof is 0.45-0.65% of the mass of the basic raw material; when the foaming agent is sodium percarbonate, the amount thereof is 11-13% of the mass of the basic raw material.
[0015] According to a preferred embodiment of the present invention, the foaming agent is preferably hydrogen peroxide; this is because the electrolytic manganese slag contains more heavy metal elements, which will catalyze the reaction of hydrogen peroxide, quickly decompose uniform oxygen bubbles, and achieve a foaming effect. Hydrogen peroxide usually produces a good foaming effect on the electrolytic manganese slag; when the foaming effect of hydrogen peroxide is not good, sodium percarbonate can be used as a slow-release foaming agent; when the foaming effect of sodium percarbonate is also not good, aluminum powder commonly used in industry can be used for foaming; aluminum powder reacts with an aqueous solution of sodium hydroxide to produce hydrogen to achieve a foaming effect.
[0016] Preferably, in the foaming agent, the hydrogen peroxide is commercially available industrial hydrogen peroxide with a concentration of about 30%; the purity of the aluminum powder is ≥99.7% and the mesh number is 325 mesh (particle size ≤44 μm); and the sodium percarbonate is commercially available industrial pure.
[0017] According to a preferred embodiment of the present invention, the foam stabilizer is at least one of Diaopai soap powder, Gongnong soap powder and sodium stearate, and the amount of the foam stabilizer is 0.75-1.25% of the mass of the basic raw material.
[0018] The foam stabilizers selected in the present invention have good foam stability, maintain the volume and structure of the foam, make the foam density (the thermal insulation performance of the material with too low density is poor, and the strength of the material with too high density is low) and the foaming ratio moderate, and have good wettability to inorganic powders such as electrolytic manganese slag and fly ash.
[0019] According to a preferred embodiment of the present invention, the composition of the alkaline activator is directly related to the composition of the basic raw material; specifically, when the mass proportion of electrolytic manganese slag in the basic raw material is 50-55% (including the endpoint value, preferably 50%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 7-16%, 11-26% and 40-58% of the mass of the basic raw material respectively; at this time, the alkaline activator is 58-100% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide and water glass in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within the range of 50-55%;
[0020] When the mass proportion of electrolytic manganese slag in the basic raw material is 55-65% (excluding the lower end point, preferably 60%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 8-15%, 10-16% and 51-57% of the mass of the basic raw material, respectively; at this time, the alkaline activator is 69-88% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide and water glass in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within the range of 55-65%;
[0021] When the mass proportion of electrolytic manganese slag in the basic raw material is 65-75% (excluding the lower end point, preferably 70%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 5-14%, 10-40% and 38-53% of the basic raw material respectively; at this time, the alkaline activator is 53-107% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide and water glass in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within the range of 65-75%;
[0022] When the mass proportion of electrolytic manganese slag in the basic raw material is 75-85% (excluding the lower end point, preferably 80%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 6-13%, 9-27% and 43-56% of the mass of the basic raw material, respectively; at this time, the alkaline activator is 58-96% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide and water glass in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within the range of 75-85%;
[0023] When the mass proportion of electrolytic manganese slag in the basic raw material is 85-95% (excluding the lower end point, preferably 90%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 6-12%, 8-25% and 44-53% of the mass of the basic raw material, respectively; at this time, the alkaline activator is 58-90% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide and water glass in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within the range of 85-95%;
[0024] When the mass proportion of electrolytic manganese slag in the basic raw material is 95-100% (including the endpoint value, preferably 100%), the amount of sodium hydroxide, water glass and water in the alkaline activator is 5-10%, 27-41% and 35-45% of the mass of the basic raw material, respectively. At this time, the alkaline activator is 67-96% of the mass of the basic raw material; further preferably, the amount of sodium hydroxide in the alkaline activator decreases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within a range of 95-100%; the amount of water glass increases within a preset ratio range as the mass proportion of electrolytic manganese slag in the basic raw material increases within a range of 95-100%.
[0025] The sodium hydroxide in the above-mentioned alkaline activator is commercially available analytical grade; the water glass is commercially available industrial grade. When the mass proportion of electrolytic manganese slag in the basic raw materials is 100%, the amount of fly ash used is zero.
[0026] In a second aspect, the present invention provides a method for preparing an electrolytic manganese slag-fly ash-based building thermal insulation material, comprising the following steps:
[0027] S1. Pre-treated electrolytic manganese slag and fly ash are mixed in a predetermined ratio to obtain a basic raw material, wherein the pre-treatment includes drying, grinding and screening; sodium hydroxide, water glass and water are mixed in a predetermined ratio, stirred evenly, to obtain an alkaline activator, and the alkaline activator is allowed to stand for more than 24 hours;
[0028] S2, mixing the alkali activator and the basic raw material, stirring, and preparing a geopolymer slurry;
[0029] S3, adding a foam stabilizer to the geopolymer slurry prepared in S2 and stirring, then adding a foaming agent and continuing stirring to obtain a foamed geopolymer slurry;
[0030] S4, pouring the foamed geopolymer slurry into a mold that has been pre-treated with an anti-sticking agent, the volume of the mold being larger than the volume of the foamed geopolymer slurry (thereby reserving a certain foaming space), and covering it with an anti-drying film;
[0031] S5. The curing is divided into two stages, namely, the normal temperature (25±5℃) curing stage and the medium temperature (55-85℃) curing stage. The curing time is 12-36h and 36-60h respectively. Then demould and continue to cure at 35-50℃ for 3-7d before taking out, polishing the surface and packaging for storage.
[0032] According to a preferred embodiment of the present invention, in S2, a small laboratory agitator or a cement mortar concrete mixer is used for mixing; when a small laboratory agitator is used, the mixing speed is 250-350rpm and the mixing time is 3-10min; when a cement mortar concrete mixer is used, the mixing speed is 26-30rpm and the mixing time is 5-20min.
[0033] According to a preferred embodiment of the present invention, in S3, after adding the foam stabilizer, stirring is performed using a small laboratory agitator or a cement mortar concrete mixer; when using a small laboratory agitator, the stirring speed is 250-350rpm and the stirring time is 2-5min; when using a cement mortar concrete mixer, the stirring speed is 26-30rpm and the stirring time is 2-5min.
[0034] According to a preferred embodiment of the present invention, in S3, after adding the foaming agent, stirring and foaming are performed using a small laboratory stirrer or a cement mortar concrete mixer; when a small laboratory stirrer is used and the foaming agent is hydrogen peroxide, the stirring speed is 250-350rpm and the stirring time is 15-30s; when a small laboratory stirrer is used and the foaming agent is aluminum powder, the stirring speed is 250-350rpm and the stirring time is 30-120s; when a small laboratory stirrer is used and the foaming agent is sodium percarbonate, the stirring speed is 250-350rpm and the stirring time is 15-60s;
[0035] When a cement mortar concrete mixer is used and the foaming agent is hydrogen peroxide, the stirring speed is 26-30rpm and the stirring time is 2-5min; when a cement mortar concrete mixer is used and the foaming agent is aluminum powder, the stirring speed is 26-30rpm and the stirring time is 5-15min; when a cement mortar concrete mixer is used and the foaming agent is sodium percarbonate, the stirring speed is 26-30rpm and the stirring time is 5-10min.
[0036] According to a preferred embodiment of the present invention, in S4, the anti-sticking treatment is to apply a layer of silicone oil on the inner wall of the mold to facilitate demoulding; the anti-drying film is a plastic wrap to prevent the rapid evaporation of moisture to form cracks.
[0037] (III) Beneficial effects
[0038] The invention provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which depolymerizes active Si and Al substances in the electrolytic manganese slag and fly ash through alkali excitation, so that the active Si and Al colloids are polymerized to produce a geopolymer all-inorganic gelling material with good flame retardant performance. The electrolytic manganese slag is consumed and converted into resources, thereby solving the problem caused by the large-scale accumulation of electrolytic manganese slag solid waste and the problem of poor fireproof performance of traditional organic thermal insulation materials.
[0039] Since the activity of electrolytic manganese slag is relatively low, adding a certain amount of fly ash to it can improve the mechanical properties of the thermal insulation material to a certain extent. Moreover, the raw materials are all industrial waste slag, and cement and any combustible organic components are not used. Only industrial waste slag is converted and utilized for resources, which saves costs. The raw materials used are inorganic materials, which improve the fire resistance of the product. The foam stabilizer can stabilize the foaming effect and enhance the uniformity of the pores, improve the thermal insulation performance of the thermal insulation material, the consistency of the material, and the strength of the material; the present invention uses hydrogen peroxide, aluminum powder or sodium percarbonate as a foaming agent, which can be selected according to the actual foaming situation, and effectively improves the thermal insulation performance of the enclosure structure.
[0040] The preparation method of the thermal insulation material of the present invention is simple, the preparation process is short in time and low in energy consumption, and is suitable for practical engineering applications. DETAILED DESCRIPTION
[0041] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods.
[0042] Example 1
[0043] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0044] Basic raw material: 100g electrolytic manganese slag and 100g fly ash are dry mixed, and the electrolytic manganese slag powder can pass through a 100-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. The electrolytic manganese slag accounts for 50% of the basic raw material.
[0045] Alkali activator: Sodium hydroxide, water glass and water are weighed and mixed to obtain an alkaline activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 15.2 g (accounting for 7.6% of the basic raw materials). Water glass is a commercially available industrial grade product with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 51.6 g (accounting for 25.8% of the basic raw materials). Water is tap water, and the amount used is 88.6 g (accounting for 44.3% of the basic raw materials).
[0046] Foaming agent: hydrogen peroxide, mass concentration is 30%, dosage is 5g (accounting for 2.5% of the basic raw material).
[0047] Foam stabilizer: Diao brand soap powder, dosage is 2g (accounting for 1% of the basic raw material).
[0048] The preparation method of the thermal insulation material is as follows:
[0049] (1) Slurry preparation
[0050] Evenly mix water glass, sodium hydroxide and water to prepare an alkaline activator, and let it stand for more than 24 hours.
[0051] The basic raw material is prepared by dry-mixing the electrolytic manganese slag and fly ash which have been pre-treated by drying and grinding.
[0052] The alkali activator and the basic raw material were mixed and transferred into a small laboratory stirrer for stirring at a stirring speed of 300 r / min and a stirring time of 3 min to form a geopolymer slurry.
[0053] (2) Foam stabilization and foaming
[0054] Add a foam stabilizer to a small laboratory stirrer and stir thoroughly at a stirring speed of 300 r / min for 2 min; then add a foaming agent and continue stirring at a stirring speed of 300 r / min for 60 s to obtain a foamed geopolymer slurry.
[0055] (3) Injection molding process
[0056] Pour the prepared slurry into a silicone mold brushed with silicone oil, leave a certain amount of foaming space, and cover with plastic wrap to complete the injection molding process.
[0057] (4) Maintenance and demoulding
[0058] The mold after injection molding is placed in a curing box for curing. The curing process is divided into two stages, namely, the normal temperature (25°C) curing stage and the medium temperature (70°C) curing stage. The curing time is 24h and 48h respectively before demoulding.
[0059] (5) Polishing and packaging
[0060] Place the demoulding building insulation material into a curing box, adjust the temperature of the curing box to 45°C, cure for 7 days, then take it out, sand each surface of the material flat with sandpaper, and seal it for later use.
[0061] Example 2
[0062] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0063] Basic raw material: 125g electrolytic manganese slag and 75g fly ash are dry mixed, and the electrolytic manganese slag powder can pass through a 100-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. The electrolytic manganese slag accounts for 62.5% of the basic raw material.
[0064] Alkali activator: Sodium hydroxide, water glass and water are weighed and mixed to obtain an alkali activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 20 g (accounting for 10% of the basic raw materials). Water glass is a commercially available industrial grade product with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 30 g (accounting for 15% of the basic raw materials). Water is tap water, and the amount used is 104 g (accounting for 52% of the basic raw materials).
[0065] Foaming agent: sodium percarbonate, commercially available industrial pure, dosage is 25g (accounting for 12.5% of the basic raw material).
[0066] Foam stabilizer: sodium stearate, dosage is 2g (accounting for 1% of the basic raw material).
[0067] The preparation method of the thermal insulation material is as follows:
[0068] (1) Slurry preparation
[0069] Evenly mix water glass, sodium hydroxide and water to prepare an alkaline activator, and let it stand for more than 24 hours.
[0070] The basic raw material is prepared by dry-mixing the electrolytic manganese slag and fly ash which have been pre-treated by drying and grinding.
[0071] The alkali activator and the basic raw material are mixed and transferred into a small laboratory stirrer for stirring at a stirring speed of 250 r / min and a stirring time of 3 min to form a geopolymer slurry.
[0072] (2) Foam stabilization and foaming
[0073] Add a foam stabilizer to a small laboratory stirrer and stir thoroughly at a stirring speed of 350 r / min for 3 min; then add a foaming agent and continue stirring at a stirring speed of 300 r / min for 48 s to obtain a foamed geopolymer slurry.
[0074] (3) Injection molding process
[0075] Pour the prepared slurry into a silicone mold brushed with silicone oil, leave a certain amount of foaming space, and cover with plastic wrap to complete the injection molding process.
[0076] (4) Maintenance and demoulding
[0077] The mold after injection molding is placed in a curing box for curing. The curing process is divided into two stages, namely, the normal temperature (24°C) curing stage and the medium temperature (72°C) curing stage. The curing time is 24h and 48h respectively before demoulding.
[0078] (5) Polishing and packaging
[0079] Put the demoulding building insulation materials into a curing box, adjust the temperature of the curing box to 48℃, cure for 5 days, then take them out, sand each surface of the materials with sandpaper, and seal them for later use.
[0080] Example 3
[0081] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0082] Basic raw material: 180g electrolytic manganese slag and 20g fly ash are dry mixed, and the electrolytic manganese slag powder can pass through a 100-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. Electrolytic manganese slag accounts for 90% of the basic raw material.
[0083] Alkali activator: Sodium hydroxide, water glass and water are weighed and mixed to obtain an alkali activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 24 g (accounting for 12% of the basic raw material). Water glass is a commercially available industrial grade product, with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 35 g (accounting for 17.5% of the basic raw material). Water is tap water, and the amount used is 100 g (accounting for 50% of the basic raw material).
[0084] Foaming agent: 99.7% purity aluminum powder, 325 mesh, dosage is 1.25g (accounting for 0.625% of the basic raw material).
[0085] Foam stabilizer: industrial and agricultural soap powder, dosage is 2.5g (accounting for 1.25% of the basic raw material).
[0086] The preparation method of the thermal insulation material is as follows:
[0087] (1) Slurry preparation
[0088] Evenly mix water glass, sodium hydroxide and water to prepare an alkaline activator, and let it stand for more than 24 hours.
[0089] The basic raw material is prepared by dry-mixing the electrolytic manganese slag and fly ash which have been pre-treated by drying and grinding.
[0090] The alkali activator and the basic raw material were mixed and transferred into a small laboratory stirrer for stirring at a stirring speed of 250 r / min and a stirring time of 6 min to form a geopolymer slurry.
[0091] (2) Foam stabilization and foaming
[0092] Add a foam stabilizer to a small laboratory stirrer and stir thoroughly at a stirring speed of 300 r / min for 3.5 min; then add a foaming agent and continue stirring at a stirring speed of 250 r / min for 120 s to obtain a foamed geopolymer slurry.
[0093] (3) Injection molding process
[0094] Pour the prepared slurry into a silicone mold brushed with silicone oil, leave a certain amount of foaming space, and cover with plastic wrap to complete the injection molding process.
[0095] (4) Maintenance and demoulding
[0096] The mold after injection molding is placed in a curing box for curing. The curing process is divided into two stages, namely, the normal temperature (28°C) curing stage and the medium temperature (60°C) curing stage. The curing time is 24h and 48h respectively before demoulding.
[0097] (5) Polishing and packaging
[0098] Put the demoulding building insulation materials into a curing box, adjust the temperature of the curing box to 40℃, cure for 7 days, then take them out, sand each side of the materials with sandpaper, and seal them for later use.
[0099] Example 4
[0100] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0101] Basic raw material: 3.92kg electrolytic manganese slag and 0.08kg fly ash are dry mixed, and the electrolytic manganese slag powder can pass through a 100-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. Electrolytic manganese slag accounts for 98% of the basic raw material.
[0102] Alkali activator: Sodium hydroxide, water glass and water are weighed and mixed to obtain an alkali activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 0.36 kg (accounting for 9% of the basic raw material). Water glass is a commercially available industrial grade product with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 1.4 kg (accounting for 35% of the basic raw material). Water is tap water, and the amount used is 1.18 kg (accounting for 42% of the basic raw material).
[0103] Foaming agent: 99.7% purity aluminum powder, 325 mesh, dosage is 0.024kg (accounting for 0.6% of the basic raw material).
[0104] Foam stabilizer: Diao brand soap powder, dosage is 0.042kg (accounting for 1.05% of the basic raw material).
[0105] The preparation method of the thermal insulation material is as follows:
[0106] (1) Slurry preparation
[0107] Evenly mix water glass, sodium hydroxide and water to prepare an alkaline activator, and let it stand for more than 24 hours.
[0108] The basic raw material is prepared by dry-mixing the electrolytic manganese slag and fly ash which have been pre-treated by drying and grinding.
[0109] The alkali activator and the basic raw materials are mixed and transferred into a cement mortar concrete mixer for stirring at a stirring speed of 28 r / min and a stirring time of 10 min to form a geopolymer slurry.
[0110] (2) Foam stabilization and foaming
[0111] Add a foam stabilizer to the cement mortar concrete mixer and stir it fully. The stirring speed is 28 r / min and the stirring time is 5 min. Then add a foaming agent and continue stirring. The stirring speed is 30 r / min and the stirring time is 5 min to obtain a foamed geopolymer slurry.
[0112] (3) Injection molding process
[0113] Pour the prepared slurry into a silicone mold brushed with silicone oil, leave a certain amount of foaming space, and cover with plastic wrap to complete the injection molding process.
[0114] (4) Maintenance and demoulding
[0115] The mold after injection molding is placed in a curing box for curing. The curing process is divided into two stages, namely, the normal temperature (27°C) curing stage and the medium temperature (68°C) curing stage. The curing time is 24h and 48h respectively before demoulding.
[0116] (5) Polishing and packaging
[0117] Place the demoulding building insulation material into a curing box, adjust the temperature of the curing box to 45°C, cure for 7 days, then take it out, sand each surface of the material flat with sandpaper, and seal it for later use.
[0118] Example 5
[0119] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0120] Basic raw material: 2.8kg electrolytic manganese slag and 1.2kg fly ash are dry mixed, and the electrolytic manganese slag powder can pass through a 100-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. The electrolytic manganese slag accounts for 70% of the basic raw material.
[0121] Alkali activator: weigh sodium hydroxide, water glass and water, mix and stir them thoroughly to prepare the alkaline activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 0.55 kg (accounting for 13.75% of the basic raw material). Water glass is a commercially available industrial grade product with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 0.82 kg (accounting for 20.5% of the basic raw material). Water is tap water, and the amount used is 1.97 kg (accounting for 49.25% of the basic raw material).
[0122] Foaming agent: hydrogen peroxide, mass concentration is 30%, dosage is 0.12kg (accounting for 3% of the basic raw material).
[0123] Foam stabilizer: industrial and agricultural soap powder, dosage is 0.04kg (accounting for 1% of the basic raw material).
[0124] The preparation method of the thermal insulation material is shown in Example 4 and will not be described in detail here.
[0125] Example 6
[0126] This embodiment provides an electrolytic manganese slag-fly ash-based building thermal insulation material, which is prepared from the following raw materials: basic raw materials, alkali activator, foam stabilizer and foaming agent.
[0127] Basic raw material: 3.24kg electrolytic manganese slag and 0.76kg fly ash are dry mixed, and the electrolytic manganese slag powder can pass through an 80-mesh sieve but not a 120-mesh sieve. The fly ash particle size passes through a 200-mesh sieve. The electrolytic manganese slag accounts for 81% of the basic raw material.
[0128] Alkali activator: weigh sodium hydroxide, water glass and water, mix and stir them thoroughly to prepare the alkaline activator. Sodium hydroxide is commercially available analytical grade, and the amount used is 0.44 kg (accounting for 11% of the basic raw materials). Water glass is a commercially available industrial grade product with a modulus of 2.37 and a solid content of 42.5%, and the amount used is 0.74 kg (accounting for 18.5% of the basic raw materials). Water is tap water, and the amount used is 2.12 kg (accounting for 53% of the basic raw materials).
[0129] Foaming agent: 0.108 kg of hydrogen peroxide with a mass concentration of 30% (accounting for 2.7% of the basic raw material).
[0130] Foam stabilizer: sodium stearate, dosage is 0.04kg (accounting for 1% of the basic raw material).
[0131] The preparation method of the thermal insulation material is as follows:
[0132] (1) Slurry preparation
[0133] Evenly mix water glass, sodium hydroxide and water to prepare an alkaline activator, and let it stand for more than 24 hours.
[0134] The basic raw material is prepared by dry-mixing the electrolytic manganese slag and fly ash which have been pre-treated by drying and grinding.
[0135] The alkali activator and the basic raw materials are mixed and transferred into a cement mortar concrete mixer for stirring at a stirring speed of 30 r / min and a stirring time of 10 min to form a geopolymer slurry.
[0136] (2) Foam stabilization and foaming
[0137] Add a foam stabilizer to the cement mortar concrete mixer and stir it fully. The stirring speed is 30r / min and the stirring time is 5min. Then add a foaming agent and continue stirring. The stirring speed is 30r / min and the stirring time is 5min to obtain a foamed geopolymer slurry.
[0138] (3) Injection molding process
[0139] Pour the prepared slurry into a silicone mold brushed with silicone oil, leave a certain amount of foaming space, and cover with plastic wrap to complete the injection molding process.
[0140] (4) Maintenance and demoulding
[0141] The mold after injection molding is placed in a curing box for curing. The curing process is divided into two stages, namely, the normal temperature (27°C) curing stage and the medium temperature (68°C) curing stage. The curing time is 24h and 48h respectively before demoulding.
[0142] (5) Polishing and packaging
[0143] Put the demoulding building insulation materials into a curing box, adjust the temperature of the curing box to 40℃, cure for 5 days, then take them out, sand each surface of the materials with sandpaper, and seal them for later use.
[0144] Comparative Example 1
[0145] This comparative example is based on Example 1, and the composition of the alkaline activator is changed to: 35g of sodium hydroxide (accounting for 17.5% of the basic raw material), 16g of water glass (accounting for 8% of the basic raw material), and 106g of water (accounting for 53% of the basic raw material). In this comparative example, the amount of sodium hydroxide in the alkaline activator is increased compared with Example 1, while the amount of water glass is reduced. Other steps and conditions refer to Example 1.
[0146] Comparative Example 2
[0147] This comparative example is based on Example 1, and the composition of the alkaline activator is changed to: 12g of sodium hydroxide (accounting for 6% of the basic raw material), 80g of water glass (accounting for 40% of the basic raw material), and 90g of water (accounting for 45% of the basic raw material). In this comparative example, the amount of sodium hydroxide in the alkaline activator is reduced compared with Example 1, and the amount of water glass is increased. Other steps and conditions refer to Example 1.
[0148] Comparative Example 3
[0149] This comparative example is based on Example 2, and the composition of the alkaline activator is changed to: 12g of sodium hydroxide (accounting for 6% of the basic raw material), 50g of water glass (accounting for 25% of the basic raw material), and 82g of water (accounting for 41% of the basic raw material). This comparative example is based on Example 2, and the amount of sodium hydroxide in the activator is reduced, and the amount of water glass is increased. The steps and conditions are as in Example 2.
[0150] Comparative Example 4
[0151] This comparative example is based on Example 3, and the composition of the alkaline activator is changed to: 40g of sodium hydroxide (accounting for 20% of the basic raw materials), 14g of water glass (accounting for 7% of the basic raw materials), and 104g of water (accounting for 52% of the basic raw materials). This comparative example is based on Example 3, and the amount of sodium hydroxide in the activator is increased, and the amount of water glass is reduced. Other steps and conditions refer to Example 3.
[0152] Comparative Example 5
[0153] This comparative example is based on Example 4, and the basic raw material composition is changed to: 3.6 kg of electrolytic manganese slag (accounting for 80% of the basic raw material), 0.4 kg of fly ash (accounting for 20% of the basic raw material). Alkali activator: sodium hydroxide is used in an amount of 0.36 kg (accounting for 9% of the basic raw material), water glass is used in an amount of 1.4 kg (accounting for 35% of the basic raw material), and water is used in an amount of 1.18 kg (accounting for 42% of the basic raw material).
[0154] This comparative example increases the amount of electrolytic manganese slag in the basic raw material and reduces the amount of fly ash on the basis of Example 4. The other steps and conditions refer to Example 4.
[0155] Comparative Example 6
[0156] This comparative example is based on Example 5, except that the amount of the foaming agent is changed to: 0.2 kg of hydrogen peroxide (accounting for 5% of the basic raw material). This comparative example is based on Example 5, with an increased amount of the foaming agent (hydrogen peroxide). The other steps and conditions refer to Example 5.
[0157] Comparative Example 7
[0158] This comparative example is based on Example 5, except that the foaming agent is changed to: 0.08 kg hydrogen peroxide (accounting for 2% of the basic raw material) and 0.24 kg sodium percarbonate (accounting for 6% of the basic raw material). This comparative example is based on Example 5, and the type and amount of the foaming agent are changed. The other steps and conditions refer to Example 5.
[0159] The density, combustion performance and compressive strength of the thermal insulation materials prepared above were tested in accordance with the "Code for Acceptance of Construction Quality of Energy-Saving Engineering Projects" GB50411-2019. Table 1 shows the performance indicators of the thermal insulation materials of Examples 1-6 and Comparative Examples 1-7.
[0160] Table 1
[0161]
[0162] As can be seen from the above table, the thermal insulation material of the present invention is based on electrolytic manganese slag and fly ash after pretreatment such as drying and grinding. Without adding cement, sand, reinforcing fiber, organic polymer and other materials, an alkali activator is used to promote the inorganic geopolymer reaction of the basic raw materials. The component selection and proportion of the alkali activator are strictly optimized so that the prepared thermal insulation board still has excellent compressive strength and thermal insulation performance (meeting GB50411-2019 requirements) without adding traditional reinforcing materials. The lower the thermal conductivity of the thermal insulation material, the better the thermal insulation performance, and the higher the compressive strength, the better the mechanical strength. However, in the absence of other reinforcing fibers or reinforcing materials, the thermal conductivity of the thermal insulation material is usually two inversely correlated quantities with the compressive strength. Specifically in the present invention, the composition of the alkaline activator is directly related to the mass proportion of the electrolytic manganese slag in the basic raw material. This ratio range is one of the core innovations of the present invention. When the component selection and ratio of the alkaline activator do not match the mass proportion of the electrolytic manganese slag in the basic raw material (beyond the range required by the present invention), it directly affects the thermal insulation performance or compressive strength of the thermal insulation material, which may make it difficult for the thermal insulation material to achieve both the compressive strength and low thermal conductivity required by industry standards, or even fail to form.
[0163] In addition, since cement, reinforcing fiber, organic polymer and sand (river sand is not a renewable resource) are not used, and all industrial waste is used as raw materials, the preparation cost of the thermal insulation material is low, which has significant environmental advantages. At the same time, based on the high-dosage application of electrolytic manganese slag, the present invention can effectively realize the rapid disposal and resource conversion of industrial solid waste, reducing its negative impact on the environment. The thermal insulation material after molding is an inorganic material with excellent flame retardant and fireproof properties, which can partially solve the problem of poor fireproof performance of traditional organic thermal insulation materials, and is suitable for the field of building thermal insulation with high requirements for flame retardancy.
[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrolytic manganese slag-fly ash-based building thermal insulation material, characterized in that: Prepared from the following raw materials: Basic raw materials, alkali activators, foam stabilizers and foaming agents; The basic raw material is a mixture of electrolytic manganese slag and fly ash, wherein the electrolytic manganese slag accounts for 50%-100% by weight; the powder particle size of the electrolytic manganese slag is 60-120 meshes; the powder particle size of the fly ash is 200 meshes; The alkaline activator is prepared by mixing sodium hydroxide, water glass and water; The foam stabilizer is soap powder or sodium stearate, and the particle size is 60-120 mesh; The foaming agent is at least one of hydrogen peroxide, aluminum powder and sodium percarbonate.
2. The electrolytic manganese slag-fly ash-based building thermal insulation material according to claim 1, characterized in that: When hydrogen peroxide is selected as the foaming agent, its usage is 2-3% of the mass of the basic raw material; when aluminum powder is selected as the foaming agent, its usage is 0.45-0.65% of the mass of the basic raw material; when sodium percarbonate is selected as the foaming agent, its usage is 11-13% of the mass of the basic raw material.
3. The electrolytic manganese slag-fly ash-based building thermal insulation material according to claim 2, characterized in that: The hydrogen peroxide used is commercially available industrial hydrogen peroxide; the purity of the aluminum powder is ≥99.7% and the mesh size is 325 mesh; and the sodium percarbonate is commercially available industrial pure.
4. The electrolytic manganese slag-fly ash-based building thermal insulation material according to claim 1 or 2, characterized in that: The foam stabilizer is at least one of Diaopai soap powder, Gongnong soap powder and sodium stearate, and the amount of the foam stabilizer is 0.75-1.25% of the mass of the basic raw material.
5. The electrolytic manganese slag-fly ash-based building thermal insulation material according to claim 2, characterized in that: The composition of the base activator is directly related to the composition of the base raw material; specifically, When the mass proportion of electrolytic manganese slag in the basic raw materials is 50-55%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 7-16%, 11-26% and 40-58% of the mass of the basic raw materials respectively; When the mass proportion of electrolytic manganese slag in the basic raw materials is 55-65%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 8-15%, 10-16% and 51-57% of the mass of the basic raw materials respectively; When the mass proportion of electrolytic manganese slag in the basic raw materials is 65-75%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 5-14%, 10-40% and 38-53% of the basic raw materials respectively; When the mass proportion of electrolytic manganese slag in the basic raw materials is 75-85%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 6-13%, 9-27% and 43-56% of the mass of the basic raw materials respectively; When the mass proportion of electrolytic manganese slag in the basic raw materials is 85-95%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 6-12%, 8-25% and 44-53% of the mass of the basic raw materials respectively; When the mass proportion of electrolytic manganese slag in the basic raw materials is 95-100%, the amounts of sodium hydroxide, water glass and water in the alkaline activator are 5-10%, 27-41% and 35-45% of the mass of the basic raw materials respectively.
6. A method for preparing an electrolytic manganese slag-fly ash-based building thermal insulation material, characterized in that: The raw materials are weighed and prepared according to the electrolytic manganese slag-fly ash-based building thermal insulation material according to any one of claims 1 to 5; the preparation steps are as follows: S1. Pre-treated electrolytic manganese slag and fly ash are mixed in a predetermined ratio to obtain a basic raw material, wherein the pre-treatment includes drying, grinding and screening; sodium hydroxide, water glass and water are mixed in a predetermined ratio, stirred evenly, to obtain an alkaline activator, and the alkaline activator is allowed to stand for more than 24 hours; S2, mixing the alkali activator and the basic raw material, stirring, and preparing a geopolymer slurry; S3, adding a foam stabilizer to the geopolymer slurry prepared in S2 and stirring, then adding a foaming agent and continuing stirring to obtain a foamed geopolymer slurry; S4, pouring the foamed geopolymer slurry into a mold that has been pre-treated with an anti-sticking agent, the volume of the mold being larger than the volume of the foamed geopolymer slurry, and covering the anti-drying film; S5. The curing is divided into two stages, namely the room temperature curing stage and the medium temperature curing stage. The curing time is 12-36h and 36-60h respectively before demolding; the room temperature is 25±5℃, and the medium temperature is 55-85℃; after demolding, continue to cure at 35-50℃ for 3-7d, then take out, polish the surface flat, and package for storage.
7. The preparation method according to claim 6, characterized in that: In S2, a small laboratory mixer or a cement mortar concrete mixer is used for mixing; when a small laboratory mixer is used, the mixing speed is 250-350 rpm and the mixing time is 3-10 min; when a cement mortar concrete mixer is used, the mixing speed is 26-30 rpm and the mixing time is 5-20 min.
8. The preparation method according to claim 6, characterized in that: In S3, after adding the foam stabilizer, a small laboratory agitator or a cement mortar concrete mixer is used for stirring; when a small laboratory agitator is used, the stirring speed is 250-350rpm and the stirring time is 2-5min; when a cement mortar concrete mixer is used, the stirring speed is 26-30rpm and the stirring time is 2-5min.
9. The preparation method according to claim 8, characterized in that: In S3, after adding the foaming agent, stirring is performed using a small laboratory stirrer or a cement mortar concrete mixer for stirring and foaming; when a small laboratory stirrer is used and the foaming agent is hydrogen peroxide, the stirring speed is 250-350 rpm and the stirring time is 15-30 s; when a small laboratory stirrer is used and the foaming agent is aluminum powder, the stirring speed is 250-350 rpm and the stirring time is 30-120 s; when a small laboratory stirrer is used and the foaming agent is sodium percarbonate, the stirring speed is 250-350 rpm and the stirring time is 15-60 s; When a cement mortar concrete mixer is used and the foaming agent is hydrogen peroxide, the stirring speed is 26-30rpm and the stirring time is 2-5min; when a cement mortar concrete mixer is used and the foaming agent is aluminum powder, the stirring speed is 26-30rpm and the stirring time is 5-15min; when a cement mortar concrete mixer is used and the foaming agent is sodium percarbonate, the stirring speed is 26-30rpm and the stirring time is 5-10min.
10. The preparation method according to claim 6, characterized in that: In S4, the anti-sticking treatment is to apply a layer of silicone oil on the inner wall of the mold to facilitate demoulding; the anti-drying film is a plastic wrap to prevent the rapid evaporation of moisture to form cracks.
Citation Information
Patent Citations
Electrolytic manganese residue-red mud concrete material as well as preparation method and application thereof
CN117865625A
Electrolytic manganese residue-chromium residue synergetic recycling utilization method and prepared cementing material
CN118388154A